2019
DOI: 10.1111/hepr.13296
|View full text |Cite
|
Sign up to set email alerts
|

Presence of varices in patients after hepatitis C virus eradication predicts deterioration in the FIB‐4 index

Abstract: Aims: The liver function of patients with hepatitis C virus (HCV)infection who obtained sustained virologic response (SVR) has been known to improve after HCV eradication. However, a predictor of liver function after SVR has not been definitively identified. The aim of this retrospective study was to identify a predictor of deteriorated liver function and Fibrosis-4 (FIB-4) index after SVR was achieved by direct-acting antiviral (DAA) treatment.Methods: This study retrospectively enrolled 248 patients who obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 15 publications
(18 reference statements)
2
22
0
Order By: Relevance
“…Recently, Seko et al . reported that the presence of varices was an independent predictor of deterioration of the FIB‐4 index after successful HCV eradication by DAAs . Additionally, Mauro et al .…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Seko et al . reported that the presence of varices was an independent predictor of deterioration of the FIB‐4 index after successful HCV eradication by DAAs . Additionally, Mauro et al .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the shunts are also responsible for ascites formation through impaired improvement of liver dysfunction, as well as underling portal hypertension. Similar results were reported by Seko et al ., in that in patients who showed SVR after DAA therapy, the presence of varices was an independent predictor of deterioration of the FIB‐4 index . In contrast, El‐Sherif et al .…”
Section: Discussionmentioning
confidence: 99%
“…Improvements of hepatic function and prognosis are expected by viral eradication in HCV-infected patients. [8][9][10][11] Therefore, effective and safe antiviral therapies for patients with HCV-related decompensated cirrhosis are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with decompensated cirrhosis are at high risk for development of HCC, bleeding diatheses, and fulminant infections. Improvements of hepatic function and prognosis are expected by viral eradication in HCV‐infected patients 8–11 . Therefore, effective and safe antiviral therapies for patients with HCV‐related decompensated cirrhosis are needed.…”
Section: Introductionmentioning
confidence: 99%